ANALYSIS OF THE EFFECTIVENESS AND EFFICIENCY OF BUDGET MANAGEMENT AT THE POPULATION AND CIVIL REGISTRATION OFFICE OF INDRAGIRI HILIR REGENCY - Sami Cahyani; Raju Maulana; S.M Guntur (Indragiri Research Center (ingreat), 2026)
This study aims to analyze the level of effectiveness and efficiency of budget management at the Population and Civil Registration Office of Indragiri Hilir Regency during the period of 2022–2024. Good budget management is one of the important indicators in realizing transparent, accountable, and performance-oriented governance. The research method used is a quantitative approach with a descriptive type of research. The data used consisted of primary data obtained through questionnaires and observations, as well as secondary data in the form of budget realization reports, budget implementation documents, and regional financial statements. The data analysis technique is carried out using quantitative descriptive analysis through the calculation of the effectiveness ratio and efficiency ratio which are then categorized based on the applicable assessment standards. The results of the study show that the level of effectiveness of budget management is in the effective category with an average of 95.5%. Meanwhile, the level of budget management efficiency is in the category of quite efficient with an average of around 88.6%. This shows that budget management has been able to achieve the set targets with relatively optimal use of resources. However, there are still several obstacles such as increasing operational costs and the need to optimize internal supervision. Therefore, improvements are needed in budget planning, improvement of the supervision system, and optimization of the use of information technology to improve the efficiency of budget management in the future